Arrests Among Extreme Risk Protection Order Respondents in Washington State: A Statewide Retrospective Cohort Study - Julia P. Schleimer PhD, MPH; Nicole Asa MPH; April Zeoli PhD, MPH; Shannon Frattaroli PhD, MPH; Ali Rowhani-Rahbar MD, PhD, MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Extreme risk protection orders (ERPOs) are civil restraining orders that aim to prevent firearm-related harm by temporarily separating firearms from people at high and imminent risk of harming themselves or others. We examined arrests for any crime, violent crimes, and firearm-related crimes among ERPO respondents over time in relation to the ERPO. This was a retrospective cohort study of all individuals issued an ERPO in Washington state from 12/8/2016 to 10/2/2020, with follow-up on arrests through 7/1/2023. Exposures were ERPO respondent and case characteristics and time relative to ERPO filing: (1) 1 year prior to ERPO; (2) precipitating event window (4 days before-4 days after ERPO filing); (3) during the remainder of ERPO; and (4) 1 year after ERPO expiration. Outcomes were arrests for any crime, violent crime, and firearm-related crime. There were 488 ERPO respondents. Approximately 18.0% of respondents (n = 88) were arrested during the year prior to ERPO (0.72 arrests per 1000 person-days, 95% CI = 0.60-0.85), 18.0% (n = 88) during the 9-day precipitating event window (20.81 arrests per 1000 person-days, 95% CI = 16.80-25.49), 19.5% (n = 95) during the remainder of ERPO (1.07 arrests per 1000 person-days, 95% CI = 0.92-1.23), and 10.3% (n = 48) in the year after ERPO (0.46 arrests per 1000 person-days, 95% CI = 0.37-0.58). Results were similar for violent and firearm-related arrests. Results suggest that ERPOs are being used when respondents are behaving dangerously and that more can be done to leverage ERPO as an intervention point to address underlying and ongoing causes of criminalized or other high-risk behavior.